2021
DOI: 10.1002/rmv.2244
|View full text |Cite
|
Sign up to set email alerts
|

A rapid review of measures to support people in isolation or quarantine during the Covid‐19 pandemic and the effectiveness of such measures

Abstract: ​Summary This rapid review aimed to identify measures available to support those in isolation or quarantine during the coronavirus disease 2019 (Covid‐19) pandemic, and determine their effectiveness in improving adherence to these recommendations and or reducing transmission. The rapid review consisted of two elements, the first was a review of guidance published by national and international agencies relating to measures to support those in isolation (due to case status) or quarantine (due to close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…A summary of the included reviews is provided in Table 1. Cardwell et al (2022) identified and assessed the effectiveness of measures to support people in isolation or quarantine during the COVID-19 pandemic, and reported on two primary studies (Kavanagh et al 2011, Kavanagh et al 2012). Patel et al (2021) evaluated the effectiveness of financial support interventions and reported on two studies (Bodas & Peleg 2020, Pichler et al 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A summary of the included reviews is provided in Table 1. Cardwell et al (2022) identified and assessed the effectiveness of measures to support people in isolation or quarantine during the COVID-19 pandemic, and reported on two primary studies (Kavanagh et al 2011, Kavanagh et al 2012). Patel et al (2021) evaluated the effectiveness of financial support interventions and reported on two studies (Bodas & Peleg 2020, Pichler et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…A systematic literature search was conducted between the 25 th – 29 th April 2022 across a range of databases for English language publications, and then 5 th −6 th May 2022 for ongoing trials and ongoing reviews. The searches were restricted to studies published after 1 st Jan 2021 as the rapid reviews by Cardwell et al (2022) and Patel et al (2021) undertook searches of the prior literature. The search databases and search dates are listed in table 5.…”
Section: Rapid Review Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 32 , 38 , 42 Given uncertainty surrounding the clinical‐ and cost‐effectiveness of RADT‐based screening programmes, as well as their feasibility, it is important that the introduction of such programmes does not divert resources from other important health and social care services as this could exacerbate health inequalities. 32 , 54 …”
Section: Discussionmentioning
confidence: 99%
“…In the population‐level screening pilots conducted in Liverpool and South Wales, there was evidence of lower uptake rates in certain populations, such as those living in deprived areas, ethnic minorities, males and young people, and in those with the highest positivity rates 32,38,42 . Given uncertainty surrounding the clinical‐ and cost‐effectiveness of RADT‐based screening programmes, as well as their feasibility, it is important that the introduction of such programmes does not divert resources from other important health and social care services as this could exacerbate health inequalities 32,54 …”
Section: Discussionmentioning
confidence: 99%